2017
DOI: 10.1039/c6ra27671g
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous cerium–zirconium oxides modified with gold and copper – synthesis, characterization and performance in selective oxidation of glycerol

Abstract: Au–Cu interaction on Ce–Zr oxides leads to the increase of activity in glycerol oxidation and selectivity to glyceric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“… Plausible surface reaction mechanism of glycerol on (a) monometallic Pt and (b) bimetallic AuCu catalysts…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… Plausible surface reaction mechanism of glycerol on (a) monometallic Pt and (b) bimetallic AuCu catalysts…”
Section: Figurementioning
confidence: 99%
“…In another study, however, Kaminski et al . found that the electronegative Au − in bimetallic AuCu/CeO 2 ‐ZrO 2 catalysts (TOF: 1236 h −1 at 60 °C and 0.6 MPa O 2 ) display tunable surface redox properties and favor the formation of Cu + and Ce 3+ on catalyst surface . The charge transfer from lattice oxygen in oxide support to Cu + and Cu 2+ leads to less pronounced UV‐Vis spectra, while it seems that the interaction existing in Cu n+ /O n− /Cu n+ oligonuclear structures enhances 240 to 640 nm responses in UV‐Vis spectra .…”
Section: Figurementioning
confidence: 99%
“…Catalytic glycerol oxidation was performed at 600 rpm, because a physical diffusion did not have crucial influence on the catalytic reaction at this stirring speed (this value was set on the base of earlier study [63]). Therefore, further experiments were carried out using this stirring speed.…”
Section: Catalytic Activity -Glycerol Oxidationmentioning
confidence: 99%
“…Due to its high functionalization, glycerol can be transformed into several value‐added products (Table ), such as lactic acid, glyceric acid, glycolic acid, oxalic acid, dihydroxyacetone, glyceraldehyde, 1,2‐propanediol, 1,3‐propanediol, 1‐propanol, acrylic acid, acrolein, syngas, mono‐, di‐, tri‐glycerides, triacetin, glycerol oligomers, and polymers . Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry as raw material for the production of pharmaceuticals, cosmetics, textiles, leather, and, in a fast‐growing niche market, as monomer for the biodegradable polymer poly‐(lactic acid) or PLA .…”
Section: Introductionmentioning
confidence: 99%